AN ANALYSIS OF STUDENTS’ ERRORS IN PRONUNCING ENGLISH VOWEL BY FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF FKIP UNIVERSITY OF RIAU - Ketut Anugrah Yudha Anugrah Yudha; Fakhri Ras Ras; M. Nababan Nababan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purposes of the study are to find out kinds of errors made by students in pronouncing English vowels and the factors why these errors occur. The population of this study was the fourth semester English student department FKIP University of Riau. The instrument used by the writer in this research was a test, tape recorder it that to record the students’ pronunciation. In analyzing the data, error analysis was used the research employed students’ errors in pronouncing English vowels into separate divisions, employing the percentage descriptive analysis to count all error and interpreting the result of the data analysis. Finally, the result of the analysis shows that students are considered “Excellent” in pronouncing English vowels. The total percentage of various errors in pronouncing English vowels is 23.33%. Keywords:  Errors Analysis, Errors in Pronunciation, and Pronouncing English Vowel